2013
DOI: 10.1016/j.micinf.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Breaking in and grabbing a meal: Anaplasma phagocytophilum cellular invasion, nutrient acquisition, and promising tools for their study

Abstract: Anaplasma phagocytophilum invades neutrophils to cause the emerging infection, human granulocytic anaplasmosis. Here, we provide a focused review of the A. phagocytophilum invasin-host cell receptor interactions that promote bacterial entry and the degradative and membrane traffic pathways that the organism exploits to route nutrients to the organelle in which it resides. Because its obligatory intracellular nature hinders knock out-complementation approaches, we also discuss current methods used to study A. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 71 publications
0
49
0
Order By: Relevance
“…These gene conversion events are critical for generating antigenic diversity and immune evasion that promotes survival and persistence in naturally-infected mammalian hosts [42,43]. A. phagocytophilum also encodes several proteins that are secreted to interact with the pathogen-containing vacuolar membrane that direct vacuolar fusion events by recruiting membrane trafficking proteins [4449], or several nucleomodulins that translocate into the nucleus, including AnkA which exerts transcriptional regulating effects on genes critical for host microbicidal activity by altering chromatin structure and perhaps DNA methylation [5056]. Other changes in host transcription with infection include a marked upregulation in chemokine and proinflammatory cytokine expression [57,58].…”
Section: Anaplasmataceaementioning
confidence: 99%
“…These gene conversion events are critical for generating antigenic diversity and immune evasion that promotes survival and persistence in naturally-infected mammalian hosts [42,43]. A. phagocytophilum also encodes several proteins that are secreted to interact with the pathogen-containing vacuolar membrane that direct vacuolar fusion events by recruiting membrane trafficking proteins [4449], or several nucleomodulins that translocate into the nucleus, including AnkA which exerts transcriptional regulating effects on genes critical for host microbicidal activity by altering chromatin structure and perhaps DNA methylation [5056]. Other changes in host transcription with infection include a marked upregulation in chemokine and proinflammatory cytokine expression [57,58].…”
Section: Anaplasmataceaementioning
confidence: 99%
“…A. phagocytophilum infection in humans, termed human granulocytic anaplasmosis (HGA), is an emerging zoonosis in the USA, Europe and Asia (reviewed by Truchan et al ., 2013). HGA presents as an acute febrile illness characterized by chills, headache, malaise, leucopenia, thrombocytopenia and elevated hepatic aminotransferases.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that caspase-1-deficient mice were more susceptible than wild-type animals to Anaplasma phagocytophilum infection (8). A. phagocytophilum causes human granulocytic anaplasmosis and colonizes neutrophils during infection (9)(10)(11)(12). However, macrophages are responsible for disease pathology.…”
mentioning
confidence: 99%